(untitled) (Palíndromo, 2022)
The article is an excerpt of the preliminary analyzes about the actions of Pibid Arte of the Federal University of Vale do São Francisco, submitted to the notice 02/2020. The aim is to demonstrate the importance of the program in the qualification of teaching work based on the dialogue between initial and continuing education based on the assumption that its actions act in a counter-hegemonic way to the current model of teacher’s education in Brazil. Based on Historical-Critical Pedagogy, Pibid Arte provided, in the period from October 2020 to April 2021, methodological procedures such as: systematized studies with readings, lectures, observation of school reality in remote education, reports with the objective of analyzing the institutional, pedagogical and political dynamics that involve the teaching praxis. The first results point to the incorporation of some attitudes, namely: A. investigative practice on the school reality and the students’ social and historical context; B. a greater approximation of scholarship holders to academic writing and the need for records of pedagogical practices; C. For the supervisor, record and review of the pedagogic practice; D. the recognition of the role of the school and the teacher in the systematization of knowledge for human development, highlighting the teaching of art and the specificity of its contents. Finally, it is concluded that Pibid Arte is a differentiated space to think about teacher education policies in Art, above all, constituting a movement of resistance against the precariousness of pedagogical work in progress in the country, demonstrating possibilities for future research for the strengthening of teaching.